Causal Locus of Illness and Adaptation to Family Disruptions - Nunn, Clyde Z. (Journal for the scientific study of religion, 1968)
The hypothesis is tested that in special conditions religious beliefs can function as a stablizing force on personal and social systems. The sample was drawn from an urban hospital population, using criteria that produced a largely low-income sample of mothers. The data show that under the conditions of heightened psycho-situational stress and limited resources for adaptation, mothers who located causality of illness in God, in contrast to those who viewed illness as naturalistically determined, were more likely to report a marginal rather than a difficult or a smooth adaptation to family disruptions during illness. Theoretical implications of these findings are discussed.